ETIKA POLITIK RAKYAT DAN PEMERINTAH PERSPEKTIF FIQH - Ahmad Muzakki (LP2M Universitas Ibrahimy, 2018)
Politics is a means to bring goodness and refuse damag but some unethical behavior of politicians who tend to justify any means of obtaining and sustaining power have shaped the bad stigma among society that politics is closely related to lies,tyranny and corruption. So as if there are a thick wall that became the separator between ethics and politics.Therefore, need to reaffirm the Islamic concept of political ethics of government and society in reviewing political ethics in this paper. The author did the study on the thought santri Ma`had Aly PP . Salafiyah Syafi`iyyah Sukorejo of Situbondo written in the book Fiqh Progressive. After the discussion was found that in the view of Santri Mahad Aly, a leader should always prioritize the importance of people, make a policy that leads to justice and benefit, did not anarchic to the people and must be mandate in maintaining people's trust and in using state facilities. While the people's political ethics must support and select leaders based on quality, capability, and justice, was not because of money. When leaders make mistakes so the people must submit a polite and constructive criticism.